(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides information on the environment, ways of contaminating the water of fixed assets with harmful metal ions and carcinogenic poisoning, as well as the advantages and material disadvantages of purified, physical, technological methods of their treatment. Removal of the sorption process from these methods by other methods. The author studied the conditions for obtaining biosorbents in the treatment of water and the site sorption. Natural polymers, sources and conditions of their processing are described in the production of biosorbents. The sorption properties of rice activation, mechanical harvesting and urea modification products were compared with other biosorbents. In addition, 1 g sorption capacity is extracted from sources of natural polymers by type and source of artificial metal salts. The sorption properties of biomaterials were used by the Fredlix and Lingmur isothermal model methods. A SHIMADZU (UV-190) spectrophotometer was used to estimate the amount of metal ion absorbed.